Microwave ablation and synchronous transarterial chemoembolization combined with PD-1 inhibitor in patients with hepatocellular carcinoma following tyrosine kinase inhibitor intolerance - Shi, Qin; Zhou, Xin; Zhang, Zihan; Zhang, Wen; Ma, Jingqin; Yang, Minjie; Yu, Jiaze; Luo, Jianjun; Liu, Lingxiao; Yan, Zhiping (Frontiers in Immunology, 2023)
Purpose To determine the safety and efficacy of microwave ablation (MWA) and synchronous transarterial chemoembolization (TACE) combined with or without PD-1 inhibitor in patients with hepatocellular carcinoma (HCC) following tyrosine kinase inhibitor (TKI) intolerance. Materials and methods This study retrospectively enrolled TKI-intolerant HCC patients who underwent MWA-TACE combined with PD-1 inhibitor (MTP) or MWA-TACE (MT) from January 2019 to June 2021. MWA and TACE were performed simultaneously, and PD-1 inhibitor was administered intravenously at a dose of 200 mg once every three weeks after MWA-TACE. Adverse events (AEs) related to treatment were recorded during the follow-up. Progression-free survival (PFS) and overall survival (OS) were compared between the two groups. Results A total of 87 patients were included and classified into the MTP group (n =42) and MT group (n=45). Complications related to MWA-TACE in the MTP group were similar to that in the MT group (21.4% vs. 24.4%, P = 0.738). Moreover, 35 (83.3%) patients had eighty-four AEs related to PD-1 inhibitor in the MTP group, and 8 (19.0%) patients developed grade 3. Patients who underwent MWA-TACE combined with PD-1 inhibitor had better PFS (median, 10.0 vs. 4.7 months, P < 0.001) and OS (median, 17.0 vs. 8.5 months, P < 0.001) than those who underwent MWA-TACE alone. Treatment method and Child-Pugh class were independent prognostic factors for survival in the univariate and multivariate analysis. Conclusion MWA and synchronous TACE combined with PD-1 inhibitor might be a favorable treatment option in TKI-intolerant HCC patients.